Consumer acceptance of irradiated food and information disclosure – A retail imperative. (November 2021) - D'Souza, Clare; Apaolaza, Vanessa; Hartmann, Patrick; Brouwer, Anne Renée; Nguyen, Ninh
Abstract: There is substantial contribution in the literature for understanding the complex nature of irradiated foods, the growing importance and the controversial views expended by consumers, yet acceptance of these foods for many have not met with optimal recognition. The study extends the theory of planned behaviour antecedents to analyse independent determinants and the influences of risk and trust. The indirect effects are also examined. The study uses multigroup analyses to identify whether consumer's concerns on information for irradiated foods act as moderators in order to provide a better explanatory power. The data was analysed using Structural Equation Modelling on responses obtained from a sample of 322 consumers. The study found that the theory of planned behaviour antecedents successfully predicted behavioural intention for irradiated foods but with some limitations. The findings also demonstrate additional support to show that the robustness of the TPB framework is effective for irradiated foods and addresses the literature calls on research for more theoretical underpinnings. It further addresses retailer implications, as the ultimate decision falls with retailers who assess whether sales for irradiated foods are acceptable depending on consumer demand. Highlights: Mixed reviews regarding irradiated foods for consumer acceptance. Theory of planned behaviour antecedents successfully predicted behavioural intention for irradiated foods. Information moderates the relationship between antecedents of planned behaviour and customer acceptance. Retailers should be better prepared to provide information on irradiated foods.